Long-term multisystemic sequelae post-hospitalisation for Omicron COVID-19 vs influenza: A retrospective cohort study - Liang En Wee; Reen Wan Li Ho; Jue Tao Lim; Calvin J Chiew; David Chien Boon Lye; Kelvin Bryan Tan (International Journal of Infectious Diseases, 2025)
Objectives: To contrast long-term sequelae post-COVID-19 hospitalisations attributed to Omicron, vs seasonal influenza; stratified by vaccination. Methods: Retrospective population-based cohort study in Singapore, including all adult COVID-19 hospitalisations post-Omicron emergence (1st January 2022-3rd September 2023), and historical influenza hospitalisations (1st January 2017-3rd September 2023). Risks of post-acute diagnoses/symptoms 31-300 days post-COVID-19 hospitalisation, vs influenza, were estimated using overlap-weighted competing-risks-regression, with death as a competing risk. Results: 70,628 COVID-19 hospitalisations and 10,454 influenza hospitalisations were included. Lower overall risk of post-acute cardiac symptoms (adjusted-hazards-ratio, aHR = 0.77 [95% CI = 0.64-0.92]; P < 0.001) was observed following any COVID-19 hospitalisation vs influenza. Similarly, lower risk of any post-acute cardiac diagnosis/symptom (aHR = 0.80 [95% CI = 0.68-0.94]; P < 0.001) was observed following unboosted COVID-19 hospitalisations vs unvaccinated influenza, and lower risk of other cardiac disorders (e.g., heart failure) was observed following boosted COVID-19 hospitalisations vs vaccinated influenza (aHR = 0.58 [95% CI = 0.39-0.86]; P < 0.001), However, risks of post-acute cognitive impairment and fatigue/malaise were significantly higher post-COVID-19 vs influenza (cognition: aHR = 1.34 [95% CI = 1.08-1.68]; P < 0.001; fatigue/malaise: aHR = 1.75 [95% CI = 1.23-2.50]; P < 0.001) and when unboosted COVID-19 was compared against unvaccinated influenza (memory/cognition: aHR = 1.67 [95% CI = 1.27-2.19; P < 0.001]; fatigue/malaise: aHR = 1.77 [95% CI = 1.18-2.64]; P < 0.001). Conclusion: Risks of cognitive impairment/fatigue were increased while risk of cardiac sequelae was significantly lower post-COVID-19 vs influenza in unboosted/unvaccinated individuals. Vaccination for COVID-19/influenza remains important during endemicity.